ΙΠΠΙΚΑ Posejdipposa na tle pieśni Pindara - Pawlak, Kamil (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2014)
The article analyses the epigrams of Poseidippos of Pella from the section of ἱππικά (71–88) compared to the equestrian and charioting epinikia of Pindar. The elements, which appear in the poet of Pella’s works, can be found in epinikion poetics and thus two types of equestrian and charioting epigrams of Poseidippos can be distinguished. These are: a short mini-epinikion (79, 82,84) and a longer mini-epinikion (74, 78). The article discusses the unique poetics of Poseidippos’ epigrams, emphasising their close relationship to the victory odes of Simonides, Bacchylides and Pindar.
Keywords: Posejdippos; Pindar; Bakchylides; epinikion; epigram; hippika